2020
DOI: 10.22270/jddt.v10i1-s.3858
|View full text |Cite
|
Sign up to set email alerts
|

Determination of microbial load, total Phenolic and flavonoids contents in polyherbal formulation “yograj guggulu vati”

Abstract: Yograj guggulu vati (YGV), a polyherbal formulation is recommended for the management of diseases like arthritic, anodyne or analgesic, spasm, muscle relaxant, flatulence, digestive problem, cough, hyperglycaemia, fat burner and obesity. Though Yograj guggulu vati is widely used for the treatment of diseases in Ayurvedic System of Indian Medicine, but till date, it’s Phenolic and flavonoids contents and contamination studies have not been carried. In the present article, we evaluated the total phenolic and fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…DPPH solution measures the electron-donating ability of the herbal molecules. The activity is based upon the potential of natural products to decolourize the DPPH solution as the change in colour is directly proportional to the concentration of antioxidant [38]. In the present study, it was observed that the DPPH radical scavenging activity was positively correlated to the concentration of the extract.…”
Section: Fluorescence Analysissupporting
confidence: 56%
“…DPPH solution measures the electron-donating ability of the herbal molecules. The activity is based upon the potential of natural products to decolourize the DPPH solution as the change in colour is directly proportional to the concentration of antioxidant [38]. In the present study, it was observed that the DPPH radical scavenging activity was positively correlated to the concentration of the extract.…”
Section: Fluorescence Analysissupporting
confidence: 56%
“…Took 0.2 mL extract to determine the total phenol content. The total phenolics content of the extract was determined using the Folin-Ciocalteu method 25 . The standard curve was established as:…”
Section: Total Phenolics Extractionmentioning
confidence: 99%
“…Preparation of blank solution: Taken 2 ml of methanol, added 0.1 ml aluminium chlorides and 0.1ml of sodium acetate, & then added 2.8 ml of distilled water. After taking absorbance of standard dilution as mentioned above, draw a calibration curve and finded out the regression equation and calculated the total flavonoid content 7 . The standard curve of quercetin is shown in figure 1.…”
Section: Determination Of Flavonoid Contentsmentioning
confidence: 99%
“…The microbial load was determined as per procedure of Dutt et al 2020 7,9 . The medium was autoclaved at 151lbs per square inch pressure at 121 °C.…”
Section: Determination Of Microbial Counts Explained As Per Whomentioning
confidence: 99%